Marketing-entrepreneurship interface in small and medium size enterprises: the case of Singapore - Foo, Hee Luan (2004)
Marketing and entrepreneurship may be described as being both sides of the same coin. Both are different and yet similar. While their focus may differ, both need to co-exist in a firm as they complement and overlap each other. However, the extent of the overlap will depend on contextual issues such as the type of economy, the stage of economic development, the type of entrepreneurial activity pursued and the strategic orientation of the firm.